SARS-CoV-2 antibody prevalence, titres and neutralising activity in an antenatal cohort, United Kingdom, 14 April to 15 June 2020 - Lumley, SF; Eyre, DW; McNaughton, AL; Howarth, A; Hoosdally, S; Hatch, SB; Kavanagh, J; Chau, KK; Downs, LO; Cox, S; Dunn, L; Justice, A; et al. (European Centre for Disease Prevention and Control, 2020)
SARS-CoV-2 IgG screening of 1,000 antenatal serum samples in the Oxford area, United Kingdom, between 14 April and 15 June 2020, yielded a 5.3% seroprevalence, mirroring contemporaneous regional data. Among the 53 positive samples, 39 showed in vitro neutralisation activity, correlating with IgG titre (Pearson's correlation p<0.0001). While SARS-CoV-2 seroprevalence in pregnancy cohorts could potentially inform population surveillance, clinical correlates of infection and immunity in pregnancy, and antenatal epidemiology evolution over time need further study.